PENERAPAN JARIMATIKA DALAM PENINGKATAN KEMAMPUAN BERHITUNG PERKALIAN KELAS 3 MI MUHAMMADIYAH KALITENGAH - Rahayu, Tri Berkah; Suciana, Dola (Prosiding Temu Ilmiah Nasional Guru, 2023)
This research was carried out because the ability of grade 3 students at MI MuhammadiyahKalitengah in calculating multiplication was still low. It aims to determine the impact on the ability tocalculate multiplication using the way of jarimatika. The population used is the same as the sample,namely grade 3 at MI Muhammadiyah Kalitengah with a total of 21 students. Researchers got data fromobservations in class and evaluation tests at the end of the study. Then it was tested with the T OneSample t-test method by the researcher to find out the impact of using jarimatics on multiplicationmaterial. Based on this research, it was found that there was an impact of using jarimatics on the abilityto calculate multiplication of students which had increased. This is shown from the results of the ti test,the t value is 5.93 higher than the ti table, namely 2.08 (5.93 > 2.08) with a significance level of 0.5.Researchers can conclude that using jarimatics has a good impact on the ability to calculate themultiplication of grade 3 students at MI Muhammadiyah Kalitengah